Seasonal variation of asthma control, lung function tests and allergic inflammation in relation to vitamin D levels: a prospective annual study - Batmaz, Sehra Birgül; Arıkoğlu, Tuğba; Tamer, Lülüfer; Eskandari, Gülçin; Kuyucu, Semanur (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : There are scarce data about the role of vitamin D (vitD) in asthma control related to seasons and other confounders. Aim : To investigate the seasonal relationship between vitD levels and asthma control, lung function tests (LFTs) and cytokines during a 1-year period, among 7–17-year-old asthmatic children. Material and methods : Thirty patients with asthma with house dust mite monosensitization were evaluated 3 monthly about the previous month’s health and vitD related lifestyle factors and asthma control test (ACT), spirometry and bronchial provocation test for a year. Serum vitD, vitD binding protein (VDBP), total IgE levels, absolute eosinophil and Treg counts and cytokine levels were simultaneously measured. The seasonal changes of vitD and other parameters and the relationship between 120 pooled data sets of vitD and major outcomes were evaluated. Results : Mean vitD levels, forced expiratory volume in 1 s (FEV1%) and ACT score were lowest in winter and highest in summer. Pooled vitD levels were positively correlated with pooled ACT scores, Treg counts, FEV1% values and VDBP levels and negatively with total immunoglobulin E (IgE) and interleukin-4 (IL-4) levels and bronchodilator response. VitD levels were positively associated with ACT score, and FEV1% value and negatively with serum IgE level and bronchodilator response after adjusting for confounders. Conclusions : This study revealed that asthma control measures, LFTs and IgE levels were significantly related to serum vitD levels, independent from age, body mass index, inhaled corticosteroid use, sun exposure and season among asthmatic children. Vitamin D levels showed a positive correlation with Treg counts and a negative correlation with Th2 type cytokines.